Strengthening PAUD Managers’ Capacity for Student- Centered Learning Through Workshop and Reflenctive Practice Within Kurikulum Merdeka’s Deep Learning Approach: A Community Service Intervention in Central Java - Ismatul Khasanah; Nurkamelia Mukhtar AH; Iwan Kurniawan; Muthmainnah Muthmainnah (MENARA RIAU, 2026)
Teacher-centered learning remains a persistent challenge in Indonesian early childhood education (PAUD), even though Kurikulum Merdeka gives teachers flexibility to design learning according to children's developmental stages, interests, and local contexts. This community service article reports a two-day capacity-building intervention for 90 PAUD managers in Central Java, consisting of foundation chairs, principals, and teachers. The intervention integrated conceptual seminars, structured reflective practice, contextual lesson-planning workshops, microteaching, authentic assessment development, and institutional action planning. Baseline data from the partner organization showed that 65% of the 90 respondents still relied on teacher-centered practices. Program evaluation used a descriptive mixed-methods design through participant surveys, workshop observation, product review, reflection notes, and institutional follow-up plan documents. The immediate results showed that 85% of participants reported improved understanding of student-centered learning, 80% could explain the characteristics of deep learning through mindful, meaningful, and joyful learning, 15 contextual lesson plans were developed collaboratively, authentic assessment templates were produced, and 70% of participating institutions prepared follow-up action plans. The intervention also initiated reflective dialogue and cross-institutional communication among PAUD managers. The main contribution of this article is the PRP-PAUD model, a reflective-practical mentoring model that connects problem mapping, conceptual strengthening, reflective practice, workshop products, authentic assessment, institutional commitment, and learning networks. The findings should be read as initial capacity-building outcomes, not as proof of sustained classroom-level transformation. Further mentoring, classroom observation, and implementation evaluation are needed to test the model's effect on actual pedagogical practice.